System for logistics customer service - Ochelska-Mierzejewska, Joanna (Wydawnictwo Politechniki Łódzkiej, 2013)
The main principle of CRM is a customer oriented, consider the desires and expectations. It is necessary to in-depth analysis of the needs to improve the level of customer satisfaction. In this day where the consumeris better educated, it becomes more and more demanding – expect high quality customer service, accurate information and quick access to them. Knowing the customer perfectly there is a chance to meet his expectations and even exceed them, and thanks to this gain his trust and loyalty. We can provide them with exactly the product, which is expected, since we know his preferences, we are also able to provide him with good service and support. We save the budget because the ﬁrm keep focus on the customers who give the opportunity of cooperation and eﬀort is not wasted on those who never takes advantage of our oﬀer. The article aims to show what elements should appear in the customer management systems to store level, to provide better customer service, and to reduce the cost of its maintenance thanks to better warehouse management.